Molecular determinants for the association of human hormone-sensitive lipase with lipid droplets - Han Peng; Qikui Xu; Ting Zhang; Jiakai Zhu; Jinheng Pan; Xiaoyu Guan; Shan Feng; Jianping Wu; Qi Hu (Nature Communications)
Abstract Lipid droplets (LDs) are the main cellular storage sites for triacylglycerols (TAGs), playing an important role in energy homeostasis and cell signaling. Hydrolysis of the stored TAGs begins with conversion of TAGs into diacylglycerols (DAGs) by adipose triglyceride lipase (ATGL), followed by hydrolysis of DAGs by hormone-sensitive lipase (HSL). Despite the central role of HSL in lipolysis, the molecular determinants for its LD association have remained elusive. Here, we report the cryo-EM structure of human HSL at 3.4 Å. Combining this with hydrogen-deuterium exchange mass spectrometry, biochemical and cellular assays, we identify residues 489-538, referred to as the “H-motif”, and the N-terminal 4-helix bundle of HSL as LD-binding motifs mediating direct interaction of HSL with LDs. LD binding mediated by the LD-binding motifs is independent of HSL phosphorylation catalyzed by the cAMP-dependent kinase PKA. Our findings provide insight into the LD binding mechanism of HSL, advancing our understanding of the regulation of lipolysis.